Should NHS mental health services fear the private sector? Yes. (4th October 2010) - Pollock, Allyson M
Abstract : The coalition government wants to open up the market in the NHS. Allyson Pollock thinks this will result in an impoverished and inequitable service but Elaine Murphy and Philip Sugarman ( doi:10.1136/bmj.c5385 ) believe mental health services have much to gain